2019
DOI: 10.1111/hepr.13361
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and plasma lipid responses to pemafibrate in patients with primary biliary cholangitis

Abstract: Aim Fibrate addition to ursodeoxycholic acid (UDCA) therapy has been shown to improve both liver biochemistry and long‐term prognosis in primary biliary cholangitis (PBC) patients showing an incomplete biochemical response to UDCA alone. We herein describe the clinical outcome of seven cases of PBC that received the new selective peroxisome proliferator‐activated receptor α modulator, pemafibrate, in combination with UDCA therapy to investigate the biochemical and plasma lipid responses to the drug. Methods Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In general, IC formation and its deposition leads to inflammation via interactions with leukocytes or complement and the consequent inflammation and tissue damage may lead to fibrosis. M2BPGi is a liver fibrosis marker [40,41], and ALP, ALT and AST are markers of liver damage; however, no differences were observed in these levels between the two groups. These results showed that IC does not directly lead to liver fibrosis and liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…In general, IC formation and its deposition leads to inflammation via interactions with leukocytes or complement and the consequent inflammation and tissue damage may lead to fibrosis. M2BPGi is a liver fibrosis marker [40,41], and ALP, ALT and AST are markers of liver damage; however, no differences were observed in these levels between the two groups. These results showed that IC does not directly lead to liver fibrosis and liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…12,37 Furthermore, pemafibrate, the selective PPARα modulator, has been reported to have potential as a new second-line treatment instead of bezafibrate in combined therapy with UDCA for patients with PBC who had an inadequate response to UDCA. 38 In addition, several agents including immunomodulators, bile acid regulators and anti-inflammatory/oxidative stress suppressors are additional candidates for the treatment of patients with PBC who had an inadequate response to UDCA treatment. 12 With limited treatment options, assessing the response to UDCA treatment remains key, as it is the most crucial prognosis predictor for patients with PBC.…”
Section: Discussionmentioning
confidence: 99%
“…However, some PBC patients show early deterioration, even under UDCA administration. Recently, a combination of fibrate, an antagonist of peroxisome proliferator‐activated receptors, with UDCA was reported to improve biochemical response in PBC patients showing inadequate response to UDCA alone . However, PBC still remains one of the leading causes of end‐stage liver diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a combination of fibrate, an antagonist of peroxisome proliferator-activated receptors, with UDCA was reported to improve biochemical response in PBC patients showing inadequate response to UDCA alone. 14,15 However, PBC still remains one of the leading causes of end-stage liver diseases. 4 Herein, 14.7% of the study cohort developed liver-related events during study period, with an annual incidence of liver-related Serum tyrosine and prognosis in PBC patients Hepatology Research 2020; :214-223.…”
Section: Discussionmentioning
confidence: 99%